Because the difference between any term and the previous term is a constant, this is an arithmetic sequence because of that constant which is referred to as the common difference, d. Which in this case is -35--38=-32--35=3
Any arithmetic sequence can be expressed as:
a(n)=a+d(n-1), a=initial term, d=common difference, n=term number.
In this case a=-38 and d=3 so
a(n)=-38+3(n-1) which we can simplify to
a(n)=-38+3n-3
a(n)=3n-41, so the 52nd term is:
a(52)=3(52)-41
a(52)=156-41
a(52)=115
Answer:
4-3=1
Step-by-step explanation:
it was dilated by 1
dunno what this was really askin tho
Answer:
The answer is 41
Step-by-step explanation:
400 = 900 + 625 - 1500 cos x
400 - 1525 = -1500 cos x
-1125 = -1500 cos
cos x = -1125/-1500
x = cos⁻¹ 0.75
x = 41.409622109
x ≈ 41°
Answer:
secound one good luck
Step-by-step explanation:
180=2x+y
180-y=2x
(180-y)/2=x